Наукова електротехнічна школа Львівського політехнічного інституту наприкінці ХІХ ст. – початку ХХ ст. - Лавріненко, Ольга Валеріївна (Center of Modern Pedagogy "Learning Without Boarders" (Canada), 2019)
У статті досліджено етапи формування електротехніки як науки та навчальної дисципліни у межах Національного університету "Львівська Політехніка" з моменту заснування кафедри електротехніки у 1890 р. Розкрито внесок польської наукової спільноти у розвиток різних електротехнічних напрямів, детально проаналізовано діяльність вчених та викладачів. Доведено, що завдяки їх плідній роботі були закладені підвалини наукової електротехнічної школи НУ "Львівська політехніка", що отримала свій подальший значний розвиток у другій половині ХХ ст.

The article investigates the stages of formation of electrical engineering as a science and educational discipline within the National University "Lviv Polytechnic" since the foundation of the Department of Electrical Engineering in 1890. The contribution of the Polish scientific community to the development of various electrotechnical areas is revealed, the activities of scientists and teachers are analyzed in detail. It is proved that due to their fruitful work, the foundations of the scientific electrotechnical school of Lviv Polytechnic National University were laid, which was further developed in the second half of the twentieth century.
Scientific electrotechnical school of the Lviv polytechnic institute at the end of the XІX century – the beginning of the XX century
Keywords: електротехніка; наукова школа; Львівська політехніка; Роман Дзеслевський; Станіслав Фризе; Влодзімєж Круковський; Казимир Олеарський; Габріель Сокольницький; electrical engineering; scientific school; Lviv Polytechnic; Roman Dzeslevsky; Casimir Olearskiy; Stanislav Frize; Wlodzimierz Krukowski; Gabriel Sokolnitsky